Tungsten‐Nitride‐Coated Carbon Nanospheres as a Sulfur Host for High‐Performance Lithium‐Sulfur Batteries. Issue 7 (3rd April 2019) - Liu, Honghong; Shen, Hangjia; Li, Rongrong; Liu, Siqi; Turak, Ayse; Yang, Minghui
Abstract: Lithium‐sulfur batteries have attracted wide attention, owing to their outstanding properties such as high theoretical specific capacity, low cost, and non‐toxic nature. However, the low conductivity of the sulfur cathode and its shuttling effects are still a challenge for the energy‐storage system. In this work, we describe a potential solution to address this challenge, using carbon nanospheres encapsulated in a tungsten nitride (WN) layer, interconnected with WN nanorods. After successfully synthesizing this composite in situ by using a straightforward method, we applied it as the sulfur host for lithium‐sulfur batteries. The results demonstrate a strong chemical trapping ability of the WN shell towards lithium polysulfides (LiPSs), and a strong electron‐transfer ability of the WN nanorods. Together, these effects alleviate LiPSs′ shuttling from carbon nanospheres (CNS) and give rise to a high sulfur content (70 wt %) in the as‐prepared S/WN‐CNS material. When compared to traditional S/N‐CNS electrodes, the tuned S/WN‐CNS cathodes deliver an outstanding electrochemical performance, including a high initial capacity of 1351 mAh g −1 at 0.1 C and superior long‐term cycling stability with 80 % retention of the initial capacity with 3 mg cm −2 after 500 cycles at 0.5 C. As such, a high specific capacity, excellent rate capacity, and long cycling stability are achieved. Our approach provides a path to a broad class of high‐performance Li‐S battery applications based on nanostructured WN materials. Abstract : Feeling trapped : The tuned sulfur/tungsten nitride‐carbon nanosphere (S/WN‐CNS) cathodes deliver an outstanding electrochemical performance, because of a strong chemical trapping ability of the WN shell towards lithium polysulfides and the strong electron transfer ability of the WN nanorods during the reaction